2019
DOI: 10.7150/jca.27457
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Field Cancerization in Gastric Cancer: microRNAs as Promising Biomarkers

Abstract: Background: The biological role of microRNAs (miRNAs) in field cancerization is unknown. To investigate the involvement of miRNAs in gastric field cancerization, we evaluated the expression profile of ten miRNAs and their diagnostic value. Methods: We used three groups of FFPE gastric samples: non-cancer (NC), cancer adjacent (ADJ) and gastric cancer (GC). The expression profiles of hsa-miR-10a , -miR-21, -miR-29c, -miR-135b , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 102 publications
(108 reference statements)
2
34
0
5
Order By: Relevance
“…Conversely, the other two studies addressed TNBC biological mechanisms in greater depth by identifying driver molecular alterations in the DNA methylome in comparison with non-neoplastic breast samples [17,18], using adjacent-to-tumour tissues as non-neoplastic controls. However, it has been widely reported that tissues surrounding tumours frequently appear histologically normal but show pre-neoplastic molecular alterations [19][20][21][22][23]. This phenomenon is known as the "field effect" [19].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the other two studies addressed TNBC biological mechanisms in greater depth by identifying driver molecular alterations in the DNA methylome in comparison with non-neoplastic breast samples [17,18], using adjacent-to-tumour tissues as non-neoplastic controls. However, it has been widely reported that tissues surrounding tumours frequently appear histologically normal but show pre-neoplastic molecular alterations [19][20][21][22][23]. This phenomenon is known as the "field effect" [19].…”
Section: Discussionmentioning
confidence: 99%
“…Link et al 3 reported that miR-21, miR-155, and miR-223 expression patterns gradually increase with progression of Correa's cascade by analyzing miRNA expression in gastric mucosa from patients with chronic non-atrophic gastritis, atrophic gastritis, and GC compared to normal controls. Another study showed miRNA expression in non-cancerous tissue from gastritis, adjacent normal tissue, and GC tumor to show that miR-10a, miR-21, and miR-135b expression gradually increased from non-cancerous tissue to tumor tissue 4 . Although methylation levels of miRNA genes were explored, direct comparison of miRNA in non-tumorous gastric mucosa and healthy volunteers has not been performed 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…This PCGA would characterize the genetic alterations in premalignant lesions and corresponding changes in the microenvironment across multiple tumor types for early cancer detection and prevention 1 . Although studies of premalignant lesions have been carried out [2][3][4] , the associations of miRNA with cancer-prone environments are insufficient compared to TCGA data and are mainly studied in advanced stage cancers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Moratin et al identified differentially expressed microRNAs (miRNAs) for risk stratification using oral squamous cell carcinoma FFPE tissues [27]. Pareira et al used three groups of gastric FFPE samples to evaluate the expression profiles of 10 miRNAs as potential biomarkers of gastric cancer associated with field cancerization [28]. In 2018, Yamaguchi et al identified a TP53 gene expression signature consisting of 33 genes by performing nCounter analysis on early breast cancer FFPE samples, demonstrating its prognostic power for predicting early-stage breast cancer [29].…”
Section: Introductionmentioning
confidence: 99%